2022
DOI: 10.1186/s13075-021-02652-2
|View full text |Cite
|
Sign up to set email alerts
|

The risk of malignancy in patients with IgG4-related disease: a systematic review and meta-analysis

Abstract: Background The relationship between IgG4-related disease (IgG4-RD) and the risk of malignancy is still controversial. This article focused on assessing the risk of cancer in patients with IgG4-RD by meta-analysis. Methods We conducted a systematic review of the literature and meta-analysis characterizing the associated risk of overall malignancy and four site-specific malignancies (pancreas, lung, gastric and lymphoma) in patients with IgG4-RD. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
(47 reference statements)
0
31
0
Order By: Relevance
“…Disease progression in the left eye was rapid despite high-dose oral steroid. Although malignant lymphoma was a differential diagnosis and IgG4-RD is associated with an increased risk of lymphoma, 14 the patient did not have any B symptoms (fever, night sweats, and loss of >10% of body weight over 6 months) and the diagnosis of lymphoma was not supported by histological findings. The involvement of the fellow right eye was treated promptly with rituximab and second-line immunosuppressants, which led to resolution of scleritis and choroidal mass.…”
Section: Referencesmentioning
confidence: 87%
“…Disease progression in the left eye was rapid despite high-dose oral steroid. Although malignant lymphoma was a differential diagnosis and IgG4-RD is associated with an increased risk of lymphoma, 14 the patient did not have any B symptoms (fever, night sweats, and loss of >10% of body weight over 6 months) and the diagnosis of lymphoma was not supported by histological findings. The involvement of the fellow right eye was treated promptly with rituximab and second-line immunosuppressants, which led to resolution of scleritis and choroidal mass.…”
Section: Referencesmentioning
confidence: 87%
“…One possibility is carcinogenesis due to chronic inflammation. In patients with IgG4-RD, it has been suggested that stimulation from chronic inflammation may trigger carcinogenesis, and one such pathway involves interleukin-33, which plays a role in the pathogenesis of IgG4-RD and is also associated with malignancy[ 5 - 7 ]. Tumor secretion of hormones, peptides, and cytokines or immune cross-reactivity promote the onset of autoimmune disease, widely known as paraneoplastic syndrome[ 25 ], which is separate from the carcinogenic pathway due to chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, IgG4-RD is also known to be associated with malignant tumors, and some have reported that chronic inflammatory stimulation was involved, although the exact mechanism has not been elucidated[ 5 ]. One pathway, involving interleukin-33, which plays a role in the pathogenesis of IgG4-RD, has also been reported to be associated with the development of malignancy[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With great interest, we have read the recent article “The risk of malignancy in patients with IgG4-related disease: a systematic review and meta-analysis” by Yu et al [ 1 ]. published in Arthritis Research and Therapy.…”
Section: Main Textmentioning
confidence: 99%